Research And Practical Work Licensing Information System In Bandung City Health Department - Endah Budiyati; Erni Rihyanti (Journal of Information System, Informatics and Computing, 2022)
Society is encouraged to take advantage of rapid advances in technology and informatics by both groups of individuals and organizations working for both the public and private sectors. the current era of globalization, where today's computer is very important for every activity. Along with rapidly changing situations and conditions, information plays an increasingly important role in supporting administrative work processes and bureaucratic management tasks. Administrative procedures are carried out by the Bandung City Health Office by only filling out application forms for data storage which are still done manually. Especially in the administrative process of licensing practical work activities, which so far the system is still manual. Of course this causes the storage and use of internship letters that will be sent by applicants to be less effective and efficient. The context of the problems mentioned above will be used to further examine one of the topics of the actual work permit procedure at the Bandung City Health Office.